Identification of mineral‐binding peptides that discriminate between chalcopyrite and enargite. Issue 5 (28th November 2016) - Curtis, Susan; Lederer, Franziska L.; Dunbar, W. Scott; MacGillivray, Ross T.A.
ABSTRACT: Innovative approaches to the separation of minerals and subsequent extraction of metals are imperative owing to the increasing mineralogical complexity of ore deposits that are difficult or even impossible to separate into slurries or solutions containing only the minerals or metals of interest. Low recovery of metal is typical for these complex deposits leading to significant losses to tailings. In addition, the minerals often contain impurities, some toxic, which are difficult and costly to control or manage during the processing of a concentrate or other mineral product. One example of this complex situation is the significant economic and environmental costs associated with diluting and processing copper concentrates containing arsenic (in the form of the mineral enargite, Cu3 AsS4 ) in the production of pure copper. To overcome these separation problems, we have utilized phage display to identify peptides that demonstrate selective recognition of enargite and the arsenic‐free copper sulfide, chalcopyrite. Screening of two random peptide phage display libraries resulted in the identification of an enargite‐selective peptide with the sequence MHKPTVHIKGPT and a chalcopyrite‐selective peptide with the sequence RKKKCKGNCCYTPQ. Mineral‐binding selectivity was demonstrated by binding studies, zeta potential determination and immunochemistry. Peptides that have the ability to discriminate between enargite and chalcopyrite provide a greener option for the separation of arsenic containing contaminants from copper concentrates. This represents the first step towards a major advance in the replacement or reduction of toxic collectors as well as reducing the level of arsenic‐bearing minerals in the early stages of mineral processing. Biotechnol. Bioeng. 2017;114: 998–1005. © 2016 Wiley Periodicals, Inc. Abstract : Significant economic and environmental costs are associated with processing copper concentrates containing arsenic in the production of pure copper. Curtis and co‐workers utilized phage display to identify peptides that discriminate between two copper‐containing ores that occur naturally together; the arsenic‐containing enargite and the arsenic‐free chalcopyrite. Mineral‐binding selectivity was demonstrated by binding studies, zeta potential determination and immunochemistry. Peptides that discriminate between enargite and chalcopyrite would provide a greener option for the separation of arsenic containing contaminants from copper concentrates.